A commentary on Colossians and Philemon - Hendriksen, William, d. 1982 (London, U.K. Banner of Truth, 1964)
Includes bibliographical references.
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries